Determinación de la fracción de carbono y peso específico básico de cuatro especies forestales en diferentes estadios sucesionales del Corredor Biológico Osa, Costa Rica - Navarro-Ceciliano, Marcela (Instituto Tecnológico de Costa Rica, 2011)
A wood sampling of four forestry species (Apeiba tibourbou, Guatteria amplifolia, Hyeronima alchorneoides and Tetrathyllacium macrophyllum) has benn executed in four different successonal stages (5-15 years, 15-30 years, over 30 years and primary forest) at the biologival corridor Osa, Costa Rica. The specific gravity (SG) and carbon content (CC) of each species had been determined. In reference to the SG, it was found that A. tibourbou had an amount of 0,18; G. amplifolia 0,41; H. alchorneoides 0,55 and the T. macrophyllum 0,54; moreover, the SG presented significant differences between species and only one G. amplifolia presented differences between successional stages. In regard to CC, it was found that A. tibourbou had an amount of 0,40; G. amplifolia 0,49; H. alchorneoides 0,51 and the T. macrophyllum 0,48. On other side, the CC presented significant differences between successional stages and A. tibourbou showed only significant differences of CC in comparison to the others species. There is a correlation between SG and CC of just one species, the T. macrophyllum. The SG and CC change slightly according to an increase in the successional stage, thus it does not follow a clear tendency. The SG allows grouping the successional stages in two different groups (the youngest from 5 to 15 years, and the rest of the stages). The SG and the CC are intrinsic characteristics of species, for it must be taken into consideration whenever is intended to calculate the storage of carbon of a particular species.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2011.
Keywords: Muestreo; Madera; Bosques; Flora tropical; Carbono neutral; Economía; Efecto invernadero